2015
DOI: 10.1021/bm501771e
|View full text |Cite
|
Sign up to set email alerts
|

Copolyesters Made from 1,4-Butanediol, Sebacic Acid, andd-Glucose by Melt and Enzymatic Polycondensation

Abstract: Biotechnologically accessible 1,4-butanediol and vegetal oil-based diethyl sebacate were copolymerized with bicyclic acetalized D-glucose derivatives (Glux) by polycondensation both in the melt at high temperature and in solution at mild temperature mediated by polymer-supported Candida antarctica lipase B (CALB). Two series of random copolyesters (PB x Glux y Seb and PBSeb x Glux y ) were prepared differing in which D-glucose derivative (Glux diol or Glux diester) was used as comonomer. The three parent homop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…41 During the last 5 years, Munõz-Guerra, Galbis, and coworkers have been reporting on a new series of biodegradable linear polyesters and copolyesters from bicyclic acetalized monosaccharide monomers derived from galactaric acid (58) (Scheme 8), 42,43 D-mannitol (27), 44 D-glucitol (24), and Dglucaric acid (59) (Scheme 9). 45 Homopolyesters and random copolyesters covering a broad range of compositions were obtained. The thermal properties, especially those of the copolyesters, were largely dependent on compositions and also on the functionality of the replacing sugar unit.…”
Section: Aliphatic Polyestersmentioning
confidence: 99%
“…41 During the last 5 years, Munõz-Guerra, Galbis, and coworkers have been reporting on a new series of biodegradable linear polyesters and copolyesters from bicyclic acetalized monosaccharide monomers derived from galactaric acid (58) (Scheme 8), 42,43 D-mannitol (27), 44 D-glucitol (24), and Dglucaric acid (59) (Scheme 9). 45 Homopolyesters and random copolyesters covering a broad range of compositions were obtained. The thermal properties, especially those of the copolyesters, were largely dependent on compositions and also on the functionality of the replacing sugar unit.…”
Section: Aliphatic Polyestersmentioning
confidence: 99%
“…[33][34][35][36][37] In recent years, enzymatic synthesis of sustainable polyesters from biobased monomers has attracted much attention. 5,32 Plenty of biobased polyesters have been readily prepared via enzymatic polymerization, e.g., succinate-based aliphatic polyesters, [38][39][40] 1,4 : 3,6-dianhydrohexitol-based polyesters, 41,42 vegetal oilbased polyesters, 43 sugar derived diol-based polyesters, 44,45 etc. Recently we successfully synthesized a series of renewable 2,5-bis(hydroxymethyl)furan-based polyesters by two-stage enzymatic polycondensation in diphenyl ether.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37] This is mainly due to the high melting temperatures (T m ) and low solubility of polyamides. 33 In our laboratory the hydrolase-catalyzed polymerization is actively investigated and therefore various polyesters and polyamides are successfully produced via enzymatic polymerization, e.g., saturated and unsaturated aliphatic polyesters, [38][39][40] glucose-based polyesters, 41 furan-based polyesters, 42,43 semi-aromatic oligoamides, 44 oligo(amino acid)s, 45 aliphatic polyamides [46][47][48] and poly(amide-co-ester)s. 49 The previous studies reported by our laboratory revealed that Novozym 435 (N435), which is an immobilized form of Candida antarctica Lipase B (CALB) on acrylic resin, is a robust biocatalyst for polyester and polyamide synthesis; and N435 works well with FDCA derivatives in biocatalytic polyester synthesis. 42,43 Based on these results, we are confident that N435 is also capable of catalyzing the polymerization of FDCA derivatives and aliphatic diamines.…”
Section: Introductionmentioning
confidence: 99%